2014
DOI: 10.1109/tcpmt.2014.2315761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Formic Acid Vapor <italic>In Situ</italic> Treatment Process on Cu Low-Temperature Bonding

Abstract: Low-temperature Cu/Cu direct bonding technology using formic acid vapor in situ treatment was developed. Effect of formic acid vapor treatment conditions on Cu surface and bonding was studied. Cu surface oxide was reduced using formic acid vapor in situ treatment at 150 and 200°C, respectively. With higher temperature and longer treatment time, surface reduction is more effective. Grain boundary etching was found on chemical mechanical polished Cu film after initial treatment by formic acid. However, Cu surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…that sintered with formic acid. One reasonable reason is that the Pt-catalyzed formic acid vapor is helpful for the Ag sintering via reducing the oxygen concentration by its strong reductivity [29][30][31][32][33][34][35]. In accordance of the thermal characteristic of Ag2O paste, the bonding was determined to be carried out at 160 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…that sintered with formic acid. One reasonable reason is that the Pt-catalyzed formic acid vapor is helpful for the Ag sintering via reducing the oxygen concentration by its strong reductivity [29][30][31][32][33][34][35]. In accordance of the thermal characteristic of Ag2O paste, the bonding was determined to be carried out at 160 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Since oxygen can also be generated by the decomposition of Ag 2 O, an effective reductive gas atmosphere is assumed to be necessary. Recently, we have demonstrated that a Pt-catalyzed formic acid vapor is more effective for the reduction of Cu oxides compared to the normal formic acid vapor, thanks to the generation of H radicals during catalyzation [29][30][31][32][33][34][35][36]. Its combination with Cu nanoparticles sintering can realize a low-temperature Cu bonding with a large surface-oxidation tolerance [16,36].…”
Section: Introductionmentioning
confidence: 99%
“…21 The mechanisms of the decarboxylation (eqn (1)) and decarbonylation (eqn (2)) of formic acid in the presence of metal and metal oxides are shown in Scheme 1 on the basis of previous studies on the catalysis. [21][22][23] In a low temperature low-vacuum Cu bonding process with formic acid vapors Suga et al 6,29,30 have reported that formic acid dissociates into formate and H + adsorbing on the Cu surface, and H + bonds with O 2À to form OH À . 31,32 Above ca.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, low-temperature Cu-Cu bonding has been achieved using a surface activation process based on the reduction effect with formic acid treatment. (23) Ultrasonic bonding is also an effective method because of its advantages of rapid bonding and low-temperature process. (24)(25)(26) The low-temperature Cu-Cu bonding of conventional bumps in ambient air has been investigated using ultrasonic assist with surface treatments.…”
Section: Introductionmentioning
confidence: 99%